Are credit rating agencies still relevant? Evidence on certification from Moody's credit watches - Driss, Hamdi; Massoud, Nadia; Roberts, Gordon S. (Journal of Corporate Finance, 2019)
We show that a rating agency can provide certification for corporate borrowers through the mechanism of a credit watch with direction downgrade. We find that firms with watch-preceded rating confirmations (firms for which original ratings are confirmed after a credit watch warning) experience an increase in their long-term debt financing and ramp up their investment activities following the credit watch period. These firms are able to maintain their profitability from before to after the watch period, while we find no such evidence for firms with watch-preceded rating downgrades. Among firms with confirmed ratings, those with less access to credit markets obtain more long-term debt financing at a lower cost of debt capital only in the post-watch period, indicating that rating agencies can help alleviate firm capital constraints. The certification effects persist after controlling for potential endogeneity bias.